Factors Affecting Job Satisfaction Among Employees in Amanah Saham Nasional Berhad, Federal Territory and Selangor - Mohd Razif, Moktar (2012)
In supporting the National Economic Policy (NEP) particularly in assisting the economic status of the Bumiputra, the government through Yayasan Pelaburan Bumiputra (YPB) created Permodalan Nasional Berhad (PNB) in 1978 as a mechanism to promote national unity through equal wealth distribution. Amanah Saham Nasional Berhad (ASNB) was later set up by PNB to manage funds in form of trust fund or also known as unit trust which in return would generate income for its unit holder, initially the Bumiputra through Amanah Saham Nasional Scheme. As economic status improving, many other unit trust schemes were created through ASNB and open up to other than Bumiputra. Looking into the important role and responsibility of ASNB as part of the economic mechanism, the purpose of this study is to look into factors which influence job satisfaction of its employees in serving 9 million account holders with investment worth RM120 billion. Measurement in mean and standard deviation enable analysis to be done in order to identify the main factors affecting ASNB employees’ job satisfaction. This study involves questionnaire being distributed in four ASNB offices which is in Federal Territory and Selangor. Out of 150 questionnaires, 129 respondents resulted in moderate in status. Four (4) variables perceived as important were measured involved job satisfaction (3.6537), human resource practice-salary (3.7635) and promotion (3.3255), working environment (3.4354) and personnel values (3.7175). Furthermore, the result form the Pearson Correlation Coefficient shows human resource practice-salary and promotion, working environment and personnel values had positive relationship to the job satisfaction in ASNB Federal Territory and Selangor. Linear regression also shows three most significant relationships towards the job satisfaction among ASNB Federal Territory and Selangor employees which is personnel values (β = 0.496, p = 0.000), human resource practice-salary (β = 0.293, p = 0.000) and human resource practice-promotion (β = 0.184, p = 0.002). 0.768 or 76.8% as the contributor factor towards job satisfaction were derived through the r square as the contributor factor towards job satisfaction.In this study it is found that human resources practice,working environment,and individual/personal values dimensions have influence on job satisfaction as the main factors in ASNB Federal Territory and Selangor and needed to be taken seriously for further improvement.